Alterations in cerebellar grey matter structure and covariance networks in young people with Tourette syndrome. (May 2020) - Sigurdsson, Hilmar P.; Jackson, Stephen R.; Jolley, Laura; Mitchell, Ellie; Jackson, Georgina M.
Abstract: Tourette syndrome (TS) is a childhood-onset neurological disorder characterised by the occurrence of motor and vocal tics and the presence of premonitory sensory/urge phenomena. Functional neuroimaging studies in humans, and experimental investigations in animals, have shown that the genesis of tics in TS involve a complex interaction between cortical-striatal-thalamic-cortical brain circuits and additionally appears to involve the cerebellum. Furthermore, structural brain imaging studies have demonstrated alterations in grey matter (GM) volume in TS across a wide range of brain areas, including alterations in GM volume within the cerebellum. Until now, no study to our knowledge has yet investigated how GM structural covariance networks linked to the cerebellum may be altered in individuals with TS. In this study we employed voxel-based morphometry, and a 'seed-to-voxel' structural covariance network (SCN) mapping approach, to investigate alterations in GM cerebellar volume in people with TS, and alterations in cerebellar SCNs associated with TS. Data from 64 young participants was entered in the final analysis, of which 28 had TS while 36 were age-and sex-matched healthy volunteers. Using the spatially unbiased atlas template of the cerebellum and brainstem (SUIT) atlas, we found reduced GM volume in cerebellar lobule involved in higher-order cognitive functions and sensorimotor processing, in patients. In addition, we found that several areas located in frontal and cingulate cortices and sensorimotor network in addition to subcortical areas show altered structural covariance with our cerebellar seed compared to age-matched controls. These results add to the increasing evidence that cortico-basal ganglia–cerebellar interactions play an important role in tic symptomology.